THE STORY OF ‘SILJAN THE STORK’ AS A MACEDONIAN SELF-IDENTIFYING NARRATIVE (Filološke studije, 2019)
This text raises the question of creation of the cultural and historical identity of the Macedonian nation covering the famous Macedonian folk tale about Siljan the Stork. Macedonian obstinacy and the infringement of the law and order, which must be restrained by sentencing, is metaphorically indicated with the paradigm of parental anathema and the metamorphosis of the disobedient son in the bird-stork. The characteristics of Macedonian persistence, eternity and agelessness are also accented by the symbolism of the bird migrant, the return of which is connected to the revival of the nature and the cycle of the new birth. Admittedly, the bird figure is of crucial importance for the constitution of the solar disk present on the Macedonian flag, and the whole cyclic system as a symbol of rising and rescuing from evil. Since the time of Paeonian culture, it has been considered as one of the most important cultural symbols of this part of the world and represented the good harbinger of Macedonian versatility and longevity.